Implementation of A Tuberculosis Drug-Resistant (TB RO) Case Finding Program - Isnayati Isnayati; Kodrat Pramudho; Ratih Purnamasari (Indonesian Journal of Global Health Research, 2025)
Gaps in the achievement of drug-resistant tuberculosis case detection in Cilegon City still occur. The target of 85% case detection for RO-TB has been achieved at only 31%, with an enrollment rate of 30%. Evaluation of program implementation is needed to identify obstacles and opportunities for improving outcomes. This study aimed to analyze and evaluate the implementation of the RO-TB case-finding program. This qualitative study, using a phenomenological approach, was conducted in nine community health centers (Puskesmas) in Cilegon City, Banten. Evaluation indicators include acceptability, appropriateness, fidelity, sustainability, and implementation cost. There were 25 informants in this study, including key informants, main informants and supporting informants.Data will be collected through in-depth interviews. A questionnaire will be used to gather qualitative information. The informants in this study included heads of community health centers, health department, community health workers, pulmonary specialists, business representatives, and the media. Data analysis used the Miles and Huberman principles and triangulation. The TB RO case detection program was well-received by all Community Health Centers (Puskesmas), but trained human resources were not evenly distributed, facilities and infrastructure were inadequate, targeting needed to be reviewed, and cross-sectoral collaboration was not well-established. The SWOT analysis identified strong potential support from academics to send expert teams, industry willing to channel CSR funds and develop policies supporting the program, and the mass media to promote the TB RO case detection program. To enhance the effectiveness of the Drug-Resistant Tuberculosis case finding program, providing training for health workers and regional analysis for determining relevant targets needs to be done regularly.